New vegetable varieties of Brassica rapa and Brassica napus with modified glucosinolate content obtained by mass selection approach - Coves, S.; Soengas, P.; Velasco, P.; Fernández, J. C.; Cartea, M. E. (Frontiers in Nutrition, 2023)
Glucosinolates (GSLs) constitute a characteristic group of secondary metabolites present in the Brassica genus. These compounds confer resistance to pests and diseases. Moreover, they show allelopathic and anticarcinogenic effects. All those effects are dependent on the chemical structure of the GSL. The modification of the content of specific GSLs would allow obtaining varieties with enhanced resistance and/or improved health benefits. Moreover, the attainment of varieties with the same genetic background but with divergent GSLs concentration will prompt the undertaking of studies on their biological effects. The objective of this study was to evaluate the efficacy of two divergent mass selection programs to modify GSL content in the leaves of two Brassica species: nabicol (Brassica napus L.), selected by glucobrassicanapin (GBN), and nabiza (Brassica rapa L.), selected by gluconapin (GNA) through several selection cycles. The response to selection fitted a linear regression model with no signs of variability depletion for GSL modification in either direction, but with higher efficiency in reducing the selected GSL than in the increasing. The selection was also effective in other parts of the plant, suggesting that there is a GSL translocation in the plant or a modification in their synthesis pathway that is not-organ specific. There was an indirect response of selection in other GSL; thus this information should be considered when designing breeding programs. Finally, populations obtained by selection have the same agronomic performance or even better than the original population. Therefore, mass selection seems to be a good method to modify the content of specific GSL in Brassica crops.